Pengaruh Penilaian Produk, Cash on Delivery dan Gratis Ongkos Kirim Terhadap Keputusan Pembelian Skincare Skintific di E-Commerce Shopee : Studi Kasus pada Mahasiswi Feb Universitas Labuhanbatu - Ika Utami Siregar; Zufrie Zufrie; Siti Lam’ah Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the Influence of Product Assessment, Cash On Delivery and Free Shipping on Skintific Skincare Purchasing Decisions on Shopee E-Commerce (Case Study on Feb Students of Labuhanbatu University). The number of samples is 92 respondents. This study uses validity tests, reliability tests, classical assumption tests, multiple linear regression tests, t tests, F tests, and coefficients of determination using SPSS 27. The study was conducted to examine how independent variables influence dependent variables and the percentage level of influence of research variables by distributing research questionnaires to respondents and conducting tests. The results showed that all independent variables influenced the dependent variable with all t count values> t table and significant values <0.05 with a determination level of 0.649 or 64.90% giving a positive and significant influence.